PENGARUH POPULASI TANAMAN DAN DOSIS BIOFERTILIZER EXTRAGEN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN WORTEL (Daucus carota L.) DI DATARAN RENDAH - Riema Rimanda Putri; Aluh Nikmatullah; Herman Suheri (Fakultas Pertanian Universitas Mataram, 2021)
A research with an aim to determine the effect of plant population, rate of biofertilizer ExtraGEN and their interaction on the growth and yield of carrot (Daucus carota L.) plants on the lowland was conducted. The experiment was carried out in the University of Mataram experimental field located in Narmada, West Lombok, NTB at an altitude of 136 m above the sea level from May to July 2019. The research used a Completely Randomized Factorial Design, consisting of 2 factors, namely the plant population and rate of biofertilizer ExtraGEN. The plant population consisted of 3 level : 1 plant/polybag, 3 plants/ polybag and 5 plants/polybag. The rate of biofertilizer ExtraGEN consisted of 4 levels: without biofertilizer ExtraGEN (control), with 100 ml/polybag biofertilizer ExtraGEN, with 200 ml/polybag biofertilizer ExtraGEN, and with 400 ml/polybag biofertilizer ExtraGEN. The combinations resulted in 12 interactions which were repeated 5 times. The data obtained were analyzed using Analysis of Variance (ANOVA) at 5 % significant level and followed by an Honestly Significant Difference (HSD) at the same level. The results showed that plant population affected the rate of increase in the length of petioles, total fresh weight of the roots/polybag and total dry weight of roots/polybag, but did not affect other parameters. Higher the plant population, lowered the rate of increase in length of the petioles increased the total weight of fresh roots biomass/polybag and the weight of total dry biomass/ploybag. Biomass weight per plant was obtained 4,07 g population of 1 plant/polybag, 1,37 g population of 3 plants/polybag and 0,56 g population of 5 plants/polybag. The rates of biofertilizer ExtraGEN did not affect the growth and yield of carrot plants on the lowland.